Implementation of Entrepreneurship Learning in Business Centers at the Vocational High School Level: Systematic Literature Review (SLR) - Kurnia Fatmawati; Estu Setyo Purwantiningsih; Ryzka Anggar Kusuma; Aniek Indrawati; Ludi Wishnu Wardana; Adelia Rahma (FKIP, Universitas Palangka Raya, 2023)
The purpose of this study was to determine the management of Business Centers in Vocational High Schools (2) the effectiveness of the role of Business Centers as entrepreneurship learning units in Vocational High Schools, (3) Empowerment of Business Centers as a means of fostering entrepreneurial characteristics in students. The method used in this research is Systematic Literature Review (SLR) by collecting and analyzing journals related to keywords. Based on the literature study conducted, it was found that the Management of Vocational High School Business Centers has an average of 3 sections. The first part is the photocopy room, used for the practical activities of students majoring in Office Administration and Sharia Banking, the second part is the production room, used for the practical activities of the marketing department, the third is the entrepreneurship room, used for students majoring in Marketing, but students majoring in Office Administration, Accounting, Banking Syariah is also actively involved in the management of the Business Center in the entrepreneurship space. (2) The role of the Business Center as an entrepreneurship learning unit in Vocational High Schools is very good as can be seen from the increasing enthusiasm of students in participating in entrepreneurship learning, with the Business Center students have a place to practice entrepreneurship theory that has been taught by the teacher. In addition, students become tenacious, creative and active in doing entrepreneurial assignments given by the teacher. (3) Empowerment of the Business Center as a means of cultivating entrepreneurial characteristics for students has gone well, it can be seen from some students, most of the students have been able to read business opportunities, and can manage sales finances. Thus it can foster the characteristics of an entrepreneurial spirit in students.